Calidad de servicio y satisfacción del usuario en el Gad Municipal del cantón Salcedo - Taipe De La Cruz, Sthefany Carolina (2022)
The entitled current research "Service and user satisfaction quality in the municipal GAD from Salcedo canton" had the general aim of assessing the service and user satisfaction quality. For the research fulfillment, it was made bibliographical inquiries that allowed the information collection related to the topic. Through field research, it could evidence the shortcomings, which they have the municipality, when providing services to users, who attend this public entity. It was used the deductive method to verify the existing problem. The universe of the population, which it have worked, it was established by 65,000 inhabitants, from Salcedo canton. The sample was consisted 382 users, this number helped to assess the service and user satisfaction quality. It was used the quantitative approach, because it is a research methodology that allowed the questionnaire use to collect quantifiable data and based on this perform a statistical analysis to analyze the service and user satisfaction quality, it was applied a Servqual model instrument 30 questions with related topics to the study two variables. With a non-experimental design, through cross-sectional or transactional studies, because the research was made about a concreted situation and population at a given time, it was made the respective data tabulation, through the Excel program that, after is being processed, it yielded the following results: regularly and the service quality is almost always adequate, so user satisfaction is also in the same range. In this way, when assessing the two variables, what were studied, it was concluded that 35.1% as a higher percentage determined, what regularly and almost always the service quality and user satisfaction is adequate, because the staff is friendly and polite at the time to provide the service in the municipal Decentralized Autonomous Government (GAD) from Salcedo canton. Given the existing problems, it was made an improvement plan, what consists the four strategies implementation, which will serve as a tool with the purpose of strengthening the service quality and achieving user satisfaction